Formal Codesign Methodology with Multistep Partitioning. Issue 4 (1998) - Carchiolo, Vincenza; Malgeri, Michele; Mangioni, Giuseppe
Abstract : A codesign methodology is proposed which is suitable for control-dominated systems but can also be extended to more complex ones. Its main purpose is to optimize the trade-off between hardware performance and software reprogrammability and reconfigurability. The methodology proposed intends to cover the development of the whole system. It deals in greater detail with the steps that can be made without the need for any particular assumption regarding the target architecture. These steps concern splitting up the specification of the system into a set of individually synthesizable elements, and then grouping them for the subsequent mapping stage. In order to decrease the complexity of each partitioning attempt, a two step algorithm is proposed, thus permitting a wide exploration of possible solutions. The methodology is based on the TTL language, an extension of the T-LOTOS Formal Description Technique which provides a large amount of operators as well as a formal basis. Finally, an example pointing out the complete design cycle, excepting the allocation stage is provided.